SOCS-3 negatively regulates innate and adaptive immune mechanisms in acute IL-1–dependent inflammatory arthritis - Wong, Peter K.K. (American Society for Clinical Investigation, 2006)
RA is an autoimmune disease characterized by sustained imbalance between pro- and antiinflammatory immune mechanisms. The SOCS proteins are negative regulators of cytokine signaling, but to date there has been little information on their function in disease. The generation of Socs3(–/Δvav) mice, which lack SOCS-3 in the hematopoietic and endothelial cell compartment, allowed us to explore the role of endogenous SOCS-3 during acute inflammatory arthritis. Joint inflammation in Socs3(–/Δvav) mice was particularly severe and was characterized by increased numbers of neutrophils in the inflamed synovium, bone marrow, peripheral blood, and spleen. These features were most likely due to increased production of and enhanced responsiveness to G-CSF and IL-6 during arthritis in these mice. Local osteoclast generation and bone destruction were also dramatically increased in the absence of SOCS-3, as was macrophage activation. Finally, SOCS-3 was found to negatively regulate CD4(+) T lymphocyte activation, including production of the pleiotropic cytokine IL-17. The absence of SOCS-3 therefore had dramatic effects in this disease model, with a broader impact on cellular responses than SOCS-1 deficiency. These findings provide direct in vivo evidence that endogenous SOCS-3 is a critical negative regulator of multiple cell types orchestrating inflammatory joint disease.